Shock caused by multidrug-resistant Erysipelothrix rhusiopathiae bacteremia: a rare case report and literature review - Liu, Zhenning; Zhao, Min (The Journal of Infection in Developing Countries, 2017)
Erysipelothrix rhusiopathiae infection occurs in animals and humans. It manifests primarily as a local skin lesion, which can be treated with antibiotics. Systemic infection with E. rhusiopathiae is rare, with low occurrence of bacteremia. We describe a case of E. rhusiopathiae bacteremia leading to shock and rash all over the body in a 49-year-old man with a history of finger puncture by a puffer fish bone. Interestingly, the E. rhusiopathiae cultured in this patient’s blood was resistant to multiple drugs, including penicillin G, vancomycin, and gentamicin. The patient was treated successfully with ertapenem and ceftriaxone. Although a few cases of E. rhusiopathiae bacteremia have been reported recently, cases of multidrug-resistant E. rhusiopathiae bacteremia are extremely rare.